World Report 2016 : Events of 2015 / Human Rights Watch. (Human Rights Watch, 2016)
Human Rights Watch's annual World Report 2016 highlights the armed conflict in Syria, international drug reform, drones and electronic mass surveillance and is a must-read for anyone interested in the fight to protect human rights in every corner of the globe.